ANALISIS PENGARUH RASIO PROFITABILITAS, LIKUIDITAS, DAN LEVERAGE TERHADAP RETURN SAHAM DENGAN NILAI PERUSAHAAN SEBAGAI VARIABEL INTERVENING - Dwikirana, Sekar Aditya; Prasetiono, Prasetiono (Diponegoro Journal of Management, 2016)
The purpose of this study is to know the influence of profitability, liquidity, and leverage toward stock return using firm value as intervening variable in manufactured firms registered in Indonesia Stock Exchange in period 2010-2014.Variable used in this study are profitability (ROE), liquidity (CR), and leverage (DER) as an independent variable, Stock Return as a dependent variable, and firm value (PBV) as an intervening variable. The research populations are companies that include in the manufactured firms listed in Indonesia Stock Exchange period 2010-2014 . There are 89 sample manufactured firms by using purposive sampling method. Path analysis used to be analysis technique using program SPSS 16 for windows to determine the effect of mediation. The result of this study show that ROE has positive significant influence on PBV, CR has positive influence on PBV but not significant. ROE and PBV has positive significant influence on Stock Return, CR and DER has negative influence on Stock Return but not significant . The result of sobel test show that firm value (PBV) may mediate the relation between ROE toward Stock Return.